A peptide vaccine targeting angiotensin II attenuates the cardiac dysfunction induced by myocardial infarction - Watanabe, Ryo (Sci Rep, 2017)
A peptide vaccine targeting angiotensin II (Ang II) was recently developed as a novel treatment for hypertension to resolve the problem of noncompliance with pharmacotherapy. Ang II plays a crucial role in the pathogenesis of cardiac remodeling after myocardial infarction (MI), which causes heart failure. In the present study, we examined whether the Ang II vaccine is effective in preventing heart failure. The injection of the Ang II vaccine in a rat model of MI attenuated cardiac dysfunction in association with an elevation in the serum anti-Ang II antibody titer. Furthermore, any detrimental effects of the Ang II vaccine were not observed in the rats that underwent sham operations. Treatment with immunized serum from Ang II vaccine-injected rats significantly suppressed post-MI cardiac dysfunction in MI rats and Ang II-induced remodeling-associated signaling in cardiac fibroblasts. Thus, our present study demonstrates that the Ang II vaccine may provide a promising novel therapeutic strategy for preventing heart failure.